ISOLATION AND STRUCTURE ELUCIDATION OF DAIDZEIN AND GENISTEIN FROM SIRAITIA GROSVENORII - Chaturvedula, Venkata Sai Prakash; Prakash, Indra (Asian Journal of Pharmaceutical Research and Development, 2013)
Two isoflavones were isolated by the purification of the commercial extract of Luo Han Guo (Siraitia grosvenorii) on a C-18 column using a Biotage Flash Chromatography system. The structure of the isolated compounds were characterized as 4', 7- dihydroxyisoflavone (Daidzein) and 4',5,7,-trihydroxyisoflavone (Genistein) on the basis of extensive NMR and Mass spectral data. The complete 1H and 13C NMR spectral assignments are herewith assigned for Daidzein and Genistein on the basis of 1D ( 1H and 13C) and 2D (COSY, HSQC, HMBC) NMR and high resolution mass (HRMS) spectroscopic data.